Extradition and political crimes : the use of the political offence exception in Europe - Top, Sibel (Routledge, 2025)
"This book examines the evolution and current application of the political offence exception clause to extradition in Europe. The long-standing academic exploration of terrorism has recently given way to renewed interest in the political offence exception to extradition, prompted by recent events that signal a democratic downturn globally. Despite the significant curtailment - and in some cases, the complete abolition - of the political offence exception to extradition in Europe, certain European states continue to quietly implement this exception to deny extradition requests. This work studies the development of the political offence exception in Europe by narrowing its focus from an international perspective to the European context, specifically examining the Council of Europe and the European Union, before zeroing in on the Catalan independence crisis, which offers a particularly valuable case for analysing the application of the political offence exception in the European context. By providing a detailed examination of the evolving protections for political offenders within European legal frameworks, the text updates the long overdue academic knowledge on the matter. It is therefore an essential resource for anyone interested in European criminal law and extradition in particular. It will also be of interest to researchers, academics and policy-makers working in the areas of Criminal law, Human Rights Law, Legal Theory, Criminology and Political Science"-- Provided by publisher.
Keywords: Extradition -- Europe.; Political crimes and offenses -- Law and legislation -- Europe.; elektronické knihy; electronic books